Occassional Expressions as a Rhetorical Tool in the Persuasive Discourse of Social Issue Advertising - Biržietienė, Skirmantė; Nausėdaitė, Viltė (Lietuvių kalba, 2024)
The purpose of the research is to discuss the rhetorical value of occasional expressions in Lithuanian social issue advertising (SIA). Combining rhetorical discourse analysis and interpretation techniques, the aim was to identify which occasional expressions are used to actualize the realities of the present day, to solve social problems, also to convey the needs and attitudes of society. Occasional expressions are studied as instruments that fulfill the communicative intentions of the addressee and create the persuasiveness of the discourse. The analysis showed that occasional expressions are used to highlight persistent problems that are accepted as a norm by society. It is common to recreate those expressions that are well established in the linguistic consciousness of the addressee, are associated with cultural tradition, have become a marker of identity, and therefore function as a verified argument.